Concept of Traditional Art Training Ulu Ambek in Pariaman, West Sumatra - Yulinis (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
The ulu ambek dance portrays a leader (datuk) in his steps, actions, and thoughts for the prosperity of his people. The silat-style movements in ulu ambek dance are performed by two individuals in different positions, one attacking and the other defending. However, they never make physical contact. Midway through the performance, they switch positions, with the defender taking turns to attack and the former attacker now defending. Ulu ambek dance in Pariaman is a manifestation of historical heritage to maintain its identity because it is related to the ethics and aesthetics of traditional Pariaman society. In the current condition, traditional ulu ambek art requires continuity and should be taught to the younger generation. Therefore, there needs to be a training concept that appeals to the younger generation. The training concept includes 1) Building Technical Skills, 2) Unleashing creativity, 3) Exploring Traditional Expression, 4) Strengthening Independence, and 5) Creating a Community. From these concepts, the progress made by the younger generation in building their confidence in traditional art, mainly traditional ulu ambek dance in Pariaman, is evident.